Muggle, Juggle, Snuggle, and Struggle: profiles of parenting experiences of mothers and fathers in South Korea during the COVID-19 pandemic - Ko, Kwangman; Choi, Seulki; Choi, Saeeun; Joung, Eunhee (Journal of Family Studies, 2025)
The current study expands the literature on parenting during the COVID-19 pandemic by considering how much time spent on childcare increased and how the time was perceived by mothers and fathers in South Korea. Using the perspective of family systems theory and taking a person-centered approach, this study examined how parental experiences differ according to parental gender and investigated subgroups of mothers and fathers in terms of parental experiences during the pandemic. This study also examined how those groups differ in terms of the factors of family subsystems, adaptive self-organization, and sociodemographic variables. With a sample of 372 mothers and 366 fathers in South Korea, this study employed latent profile analysis and identified four distinct subgroups of mothers and fathers: Muggle, Juggle, Snuggle, and Struggle. Some parents feel like muggles, managing short childcare times without much joy or challenge, whereas others juggle long hours with their children, finding both joy and difficulty. Some snuggle, enjoying their extended childcare time with delight, whereas others struggle, facing the hardships of prolonged childcare without much enjoyment. The overall profile patterns and the ratios of these profiles were similar for both mothers and fathers. Suggestions for future researchers, practitioners, and policy-makers are discussed.